Deferasirox drives ROS-mediated differentiation and induces interferon-stimulated gene expression in human healthy haematopoietic stem/progenitor cells and in leukemia cells - Tiziana Tataranni; Carmela Mazzoccoli; Francesca Agriesti; Luciana De Luca; Ilaria Laurenzana; Vittorio Simeon; Vitalba Ruggieri; Consiglia Pacelli; Gerardo Della Sala; Pellegrino Musto; Nazzareno Capitanio; Claudia Piccoli (Stem Cell Research & Therapy, 2019)
Abstract Background Administration of the iron chelator deferasirox (DFX) in transfusion-dependent patients occasionally results in haematopoiesis recovery by a mechanism remaining elusive. This study aimed to investigate at a molecular level a general mechanism underlying DFX beneficial effects on haematopoiesis, both in healthy and pathological conditions. Methods Human healthy haematopoietic stem/progenitor cells (HS/PCs) and three leukemia cell lines were treated with DFX. N-Acetyl cysteine (NAC) and fludarabine were added as antioxidant and STAT1 inhibitor, respectively. In vitro colony-forming assays were assessed both in healthy and in leukemia cells. Intracellular and mitochondrial reactive oxygen species (ROS) as well as mitochondrial content were assessed by cytofluorimetric and confocal microscopy analysis; mtDNA was assessed by qRT-PCR. Differentiation markers were monitored by cytofluorimetric analysis. Gene expression analysis (GEA) was performed on healthy HS/PCs, and differently expressed genes were validated in healthy and leukemia cells by qRT-PCR. STAT1 expression and phosphorylation were assessed by Western blotting. Data were compared by an unpaired Student t test or one-way ANOVA. Results DFX, at clinically relevant concentrations, increased the clonogenic capacity of healthy human CD34+ HS/PCs to form erythroid colonies. Extension of this analysis to human-derived leukemia cell lines Kasumi-1, K562 and HL60 confirmed DFX capacity to upregulate the expression of specific markers of haematopoietic commitment. Notably, the abovementioned DFX-induced effects are all prevented by the antioxidant NAC and accompanied with overproduction of mitochondria-generated reactive oxygen species (ROS) and increase of mitochondrial content and mtDNA copy number. GEA unveiled upregulation of genes linked to interferon (IFN) signalling and tracked back to hyper-phosphorylation of STAT1. Treatment of leukemic cell lines with NAC prevented the DFX-mediated phosphorylation of STAT1 as well as the expression of the IFN-stimulated genes. However, STAT1 inhibition by fludarabine was not sufficient to affect differentiation processes in leukemic cell lines. Conclusions These findings suggest a significant involvement of redox signalling as a major regulator of multiple DFX-orchestrated events promoting differentiation in healthy and tumour cells. The understanding of molecular mechanisms underlying the haematological response by DFX would enable to predict patient’s ability to respond to the drug, to extend treatment to other patients or to anticipate the treatment, regardless of the iron overload.